1978
DOI: 10.3109/13682827809011322
|View full text |Cite
|
Sign up to set email alerts
|

The bilingual child in the speech therapy clinic

Abstract: Summary The paper considers some aspects of the linguistic assessment of the alleged speech and language delayed/deviant bilingual child in the speech therapy clinic. The suggested procedures remain intentionally within the bounds of what might be achieved by therapists utilising existing materials and skills, but emphasises some factors in assessment which it is believed have been hitherto neglected. A more detailed analysis of the bilingual child's sociolinguistic background and the nature of bilingualism is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…After eliminating duplicates within and across databases, 116 articles met the electronic search criteria. The first study meeting full search criteria was published 30 years ago in 1978 16 : no studies were identified between 1950 and 1978. The 116 nonduplicate articles identified using the computer searches were then hand reviewed by the authors to verify that each publication included original empirical data on both bilingual children and children with communication disorders.…”
Section: Search Process and Data Reductionmentioning
confidence: 99%
“…After eliminating duplicates within and across databases, 116 articles met the electronic search criteria. The first study meeting full search criteria was published 30 years ago in 1978 16 : no studies were identified between 1950 and 1978. The 116 nonduplicate articles identified using the computer searches were then hand reviewed by the authors to verify that each publication included original empirical data on both bilingual children and children with communication disorders.…”
Section: Search Process and Data Reductionmentioning
confidence: 99%
“…Those with marginalized language profiles are more likely to be over-identified as language disordered (i.e., Type I error) in settings where they are underrepresented and under-identified when they would indeed benefit from support in all other settings (i.e., Type II error 65,66 ). This extends to the pathologization of otherwise normative language development, such as that of multilinguals [67][68][69] . Similarly, the assessment of multilingual children in their non-dominant language(s) can result in a mischaracterization of their abilities 70 , leading to their overrepresentation in "special education" classes [71][72][73][74] .…”
Section: Harm In Assessmentsmentioning
confidence: 99%
“…The adequate assessment of the bilingual child's language demands a good knowledge of both languages concernedit is outside t h e competence of the majority of teachers and speech therapists. What is of extreme importance is that when children from a dual language background are observed t o be slow in developing their language skills at any age, teachers should not automatically attribute the slowness t o bilingualism, thus overlooking other possible causes, such as hearing loss, psychosocial factors or the existence of a specific language learning difficulty, which will affect the learning of any language and will call for specific remedial procedures (Abudarham, 1980;Miller, 1978).…”
Section: The Question Of Bilingualismmentioning
confidence: 99%